FAKTOR-FAKTOR YANG MEMPENGARUHI KETIDAKPATUHAN PENGEMUDI SEPEDA MOTOR TERHADAP KEWAJIBAN MENYALAKAN LAMPU UTAMA PADA SIANG HARI - Nurul Huda; Loso l (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2011)
Compliance and legal awareness is one important element for the establishment of order and security in  society,  including in-traffic  activity.  In fact,  there  are many reasons  and factors that  influence people  to comply or not comply  with traffic laws in this field especially in  terms  of the  primary obligation of lights during the day. Therefore necessary socialization should be done accompanied by a strict law enforcement efforts.  Key words: compliance with the law - enforcement – order